Power Corporation Sdn. Bhd. a Case Study - A. Jalil, Dzainuddin (1997)

(untitled)
This report has been prepared to present the case study project conducted by the author for the final semester course of his UPM/YPM off-campus program for the degree of Master in Business Administration (MBA). The two-year program was jointly organised by the Faculty of Economics and Management, Universiti Putra Malaysia and Yayasan Pe1ajaran Mara. As the core subject of this case study, the author attempts to demonstrate the importance of quality customer service to the performance of a business organization. The work focusses on how customer service can be exploited as a strategic tool by a company to gain competitive advantage in the open market environment. For the case analysis, SWOT strategic analytical technique has been used to identify the company's strengths, weaknesses, opportunities and threats in the formulation of various alternative strategies as probable solutions to the problem. To verify the validity of the alternative solution, another strategic analysis methodology called the SPACE Model was used. The evaluation and selection of the best alternative strategy was based on a qualitative and quantitative methodology by using the Cost-Benefit analysis. In view of the current economic scenario where most of the Asian countries are experiencing a sudden downturn due to speculative attacks on their currencies, it become more difficult for management to forecast the market outlook both in the short and long term perspective.In today's open market environment where globalization and liberalization were the rules of the game in most of the world economics, a company regardless of its size, could not afford to stay within its domestic shores in order to survive and excell in the ever increasing competition Despite the prevailing market instability, managers could strive to improve and maintain the perfonnance of their company's businesses strategically through the promotion and enforcement of quality customer service. Without good customer service, a company would not be able to keep its competitive advantage even if the products offered are of high quality standard. Customer service would be the key focus in any business organization - today and the future. The importance of its role is unarguable because it is the primary factor towards achieving customer satisfaction. Satisfied customers will stay loyal to a company's products and services and would be less likely to be influenced by the competitors.